Autophagy as an Innate Immune Modulator - Oh, Ji Eun (The Korean Association of Immunologists, 2013)
Autophagy is a fundamental cellular process in eukaryotic cells for maintaining homeostasis by degrading cellular proteins and organelles. Recently, the roles of autophagy have been expanded to immune systems, which in turn modulate innate immune responses. More specifically, autophagy acts as a direct effector for protection against pathogens, as well as a modulator of pathogen recognition and downstream signaling in innate immune responses. In addition, autophagy controls autoimmunity and inflammatory disorders by negative regulation of immune signaling. In this review, we focus on recent advances in the role of autophagy in innate immune systems.